Implications of Inter-Individual Differences in Clopidogrel Metabolism, with Focus on Pharmacogenetics - Dahl, Marja-Liisa (Molecular Diversity Preservation International, 2010)
Increasing evidence for the role of pharmacogenetics in treatment resistance to the antiplatelet agent clopidogrel has been gained during the last years. Apart from CYP2C19 genetic polymorphisms, nongenetic factors, particularly drug-drug interactions, age and other clinical characteristics influence the interindividual variability in clopidogrel response to varying degrees. The present article reviews the so far accumulated evidence on the role of pharmacogenetic traits influencing CYP-activity as determinants of the antiplatelet response to clopidogrel, and its clinical implications. The genetic variation in CYP2C19 activity seems to influence short- and long-term antithrombotic effects of clopidogrel to a substantial extent. Prediction models for clopidogrel non-responsiveness that include CYP2C19 genotyping together with relevant non-genetic risk factors are needed to be verified for their potential benefit in individualization of antithrombotic therapy.